2022
DOI: 10.3390/rs14215573
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intra-Urban Heat Island in a Densely Populated City Using Remote Sensing: A Case Study for Manila City

Abstract: Changes in the environment occur in cities due to increased urbanization and population growth. Sustainable Development Goal (SDG) 11 is intrinsically linked to the environment, one facet of which is the need for universal access to secure, inclusive, and accessible green and public places. As urban heat islands (UHI) have the potential to negatively influence cities and their residents, existing resources and data must be used to identify and quantify these effects. To address this, we present the use of sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Also focusing on SDG 11, a case study in Manila, Philippines, assessed the urban heat island phenomenon using RS data [10]. Consistent with findings from other studies around the world, the study revealed that residential areas, asphalted and concrete roads and walkways, and certain commercial establishments and buildings exhibited higher surface temperatures compared to areas with vegetation and near bodies of water.…”
supporting
confidence: 67%
“…Also focusing on SDG 11, a case study in Manila, Philippines, assessed the urban heat island phenomenon using RS data [10]. Consistent with findings from other studies around the world, the study revealed that residential areas, asphalted and concrete roads and walkways, and certain commercial establishments and buildings exhibited higher surface temperatures compared to areas with vegetation and near bodies of water.…”
supporting
confidence: 67%
“…Therefore, considering that areas with vegetation and bodies of water mitigate the accumulated heat, while areas with exposed soil and certain construction materials increase the temperature [35][36][37][38][39][40][41], the hypotheses were raised to explain the results obtained in the Northeastern capitals, with the support of LULC images from MapBiomas [42], Figure 7. Analyzing the Fortaleza maximum SUHI, a high temperature may have occurred in the furthest region of the urban area, at PUa, with a value of 2.31, because the hottest pixel of this area had a very high temperature of approximately 30.96 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is clear that areas with vegetation and water bodies attenuate the accumulated heat. In contrast, areas with exposed soil and certain construction materials tend to increase the temperature [22,[37][38][39][40][41][42], so the hypotheses were developed to explain the results obtained in the northeastern capitals. In addition, Land Use Land Cover (LULC) images from MapBiomas [43] were used to get the percentages of each class present in each adjacent area (Table A1 and Figure 6).…”
Section: Surface Urban Heat Islandmentioning
confidence: 99%